Enablers and barriers to community pharmacists’ readiness to implement deprescribing of inappropriate medications for older adults in Qatar - Marwa Elshazly; Sondus Jawad; Ayesha Ahmed; Hager ElGeed; Kazeem Babatunde Yusuff (PLoS ONE, 2025)
There is paucity of studies focused on the enablers and barriers to community pharmacists’ readiness to deprescribe inappropriate medications for older adults in developing settings. The current study assessed the enablers and barriers to community pharmacists’ readiness to implement deprescribing of inappropriate medications for older adults. A cross-sectional survey of 252 community pharmacists was conducted in Qatar with a pre-tested 24-item questionnaire developed with the theory of domain framework. Information about perceived enablers and barriers were elicited with a 5-point Likert-type scale. The response rate was 79.4% (200/252). The majority of the community pharmacists were females (54.5%), within the age range of 20–40 years (88.0%), had BSc / BPharm as the highest educational qualification (70.5%), were full-time employee (97.0%). The top-ranked enablers of community pharmacists’ readiness to implement deprescribing were exposure to CPD on the use of deprescribing toolkits and algorithm (66%), interprofessional collaboration with physicians (60.5%) and shared electronic patient record (59.5%), and improved remuneration / re-imbursement 58%). The top-ranked barriers were lack of access to patient records (70.5%), ineffective collaboration with physicians (66.5%), lack of time due to heavy workload (65%), regulatory framework that limit expansion of clinical roles (51%) and intense focus on sales target (49%). The top-ranked enablers of community pharmacists’ readiness to implement deprescribing were exposure to CPD on the use of deprescribing toolkits and algorithm, interprofessional collaboration with physicians and shared electronic patient record. These findings bode well for the implementation of community pharmacists-led deprescribing of inappropriate medications for older adults in Qatar. However, a number of critical barriers were identified, and these will require institutional, regulatory and organizational interventions to improve readiness.